Consumer satisfaction with occupational health services: should it be measured?. Issue 4 (1st April 2001) - Verbeek, J; van Dijk, F; Räsänen, K; Piirainen, H; Kankaanpää, E; Hulshof, C
Abstract : OBJECTIVES: To find answers in the literature to the questions if, why, and how consumer satisfaction with occupational health services (OHSs) should be measured. METHODS: Publications about the concept of consumer satisfaction with health care and surveys of consumer satisfaction with occupational health care were reviewed. RESULTS: For care providers, surveys of consumer satisfaction can be useful to improve quality or as indicators of non-compliant behaviour among patients. For clients, satisfaction surveys can be helpful for choosing between healthcare providers. Satisfaction is made up of an affective component of evaluation and a cognitive component of expectations. Also, in occupational health care, patient satisfaction is measured by dimensions such as the humanness and competence of the care provider similar to health care in general. However, there are dimensions that are specific to occupational health—such as the perceived independence of the physician, unclear reasons for visiting an OHS, and the perceived extent of knowledge of OHS professionals about the patient's working conditions. Dimensions of client satisfaction are mostly similar to patient satisfaction but include more businesslike aspects. They are different for the two groups of client, employers and employees. To measure consumer satisfaction in occupational healthcare specific questionnaires must be constructed. To achieve the highest possible reader satisfaction guidelines are provided for construction of a questionnaire. CONCLUSIONS: Consumer satisfaction is a complex theoretical concept, but it is relatively easy to measure in practice and can be a valuable tool for quality improvement. Consumers' evaluations of occupational health services will become increasingly important due to changes in the organisation of occupational health care. Occupational healthcare providers are encouraged to measure the consumer satisfaction of their services.